Legal protection of the life and health of the future generation - Mokhov , Alexandr Anatolievich; Posulikhina , Natalya Semenovna; Pеkshev, Alexey Victorovich; Neznamova , Alla Andreevna; Shestov , Sergej Nikolaevich (Interacción y Perspectiva, 2023)
The article examines the problems related to the legal protection of life and health of future generations based on the methodological apparatus and international and constitutional law. Particular attention is paid to legislative approaches to the definition of the term "future generation", the difference between "needs" and "life and health", and the correlating relationship between the present and future generations. The authors of the article use legal tools to address the deep properties of the concept of future generation through the prism of fundamental principles and values of law. The discussion of the topic was conducted from the position of general scientific methods of cognition (systemic and theoretical), as well as special scientific methods: comparative jurisprudence, logical, technical, and legal analysis, concretization, and interpretation. The purpose of the study is to identify theoretical and practical problems in ensuring the protection of life and health of future generations, investigate the constitutional and legal cross-section of the definition of the future generation, and identify threats to future generations. Some principles on protection of future generations were analyzed; the differences between interests, health, and needs of future generations and the procedural prerequisites for the protection of life and health of the future generation were shown.